2019
DOI: 10.1016/j.jtho.2019.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Negative Pneumonia Augments Non–Small Cell Lung Cancer Metastasis through Host Toll-like Receptor 4 Activation

Abstract: Introduction: Surgery is essential for cure of early-stage non-small cell lung cancer (NSCLC). Rates of postoperative bacterial pneumonias, however, remain high, and clinical data suggests that post-operative infectious complications confer an increased risk for metastasis. Toll-like receptors (TLRs) mediate the inflammatory response to infection by recognizing evolutionarily conserved bacterial structures at the surface of numerous pulmonary cell types; yet, little is known about how host TLR activation influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…TLR4 is widely expressed in lung cells, bone marrow and infiltrating cells. TLR1-6 and TLR9 are highly expressed in airway epithelial cells [16][17][18]. The expression of TLR2, TLR4, TLR7/8 and TLR9 in lung cancer was significantly higher than that in normal lung [19,20].…”
Section: Treatment With Hucmscs Inhibits Inflammatory Responses In MImentioning
confidence: 91%
“…TLR4 is widely expressed in lung cells, bone marrow and infiltrating cells. TLR1-6 and TLR9 are highly expressed in airway epithelial cells [16][17][18]. The expression of TLR2, TLR4, TLR7/8 and TLR9 in lung cancer was significantly higher than that in normal lung [19,20].…”
Section: Treatment With Hucmscs Inhibits Inflammatory Responses In MImentioning
confidence: 91%
“…The results reported by Gowing et al 6 not only contribute to the understanding of adverse consequences of sepsis in lung cancer patients and propose a possible strategy to maximize the therapeutic benefit of surgery, they also provide a new insight on the interaction between microbial species present in the lungs, pre-existing inflammation, and ultimate cancer spread. TLRs, indeed, besides detecting pathogens, are highly important sensors of commensal micro-organisms, which have been recently found essential in regulating pulmonary immune microenvironment and tumor progression.…”
mentioning
confidence: 87%
“…In this issue of the Journal, Gowing et al 6 investigated the role of TLR4 activation in promoting experimental cancer metastasis after induction of gram-negative pneumonia. Using a well-established NSCLC metastatic preclinical mouse model, they induced pneumonia in mice by Escherichia coli intranasal inoculation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that specific genera might be engaged with the metastasis of lung cancer patients [13,14]. In vivo mechanistic investigations found that certain species might contribute to the development of extrathoracic or intrathoracic metastasis via enhancement of adhesion of lung cancer cell or regulation of lung immune system [15][16][17]. Therefore, it is plausible to hypothesize that the lung microbiota may be identified as relevant to N and M classification.…”
Section: Introductionmentioning
confidence: 99%